The Critical Role of AtPAP17 and AtPAP26 Genes in Arabidopsis Phosphate Compensation Network - Farhadi, Siamak; Sabet, Mohammad Sadegh; Malboobi, Mohammad Ali; Moieni, Ahmad (Frontiers in Plant Science, 2020)
Purple acid phosphatases (PAP)-encoding genes form a complex network that play a critical role in plant phosphate (Pi) homeostasis. Mostly, the functions of PAPs were investigated individually. However, the interactions of most of these genes in response to various concentrations of available Pi remain unknown. In this study, the roles of AtPAP17 and AtPAP26 genes, and their relationship within Pi homeostasis context were investigated. Surprisingly, atpap17 and atpap26 mutants not only showed no obvious developmental defects, but also produced higher biomass in compare to wild type (WT) plants under normal growth conditions. Comparing gene expression patterns of these mutants with WT plant, we identified a set of genes up-regulated in mutant plants but not in WT. Based on these unexpected results and up-regulation of AtPAP17 and AtPAP26 genes by the loss of function of each other, the hypothesis of compensation relationship between these genes in Pi homeostasis was assessed by generating atpap17/atpap26 double mutants. Observation of developmental defects in atpap17/atpap26 mutant but not in single mutants indicated a compensation relationship between AtPAP17 and AtPAP26 genes in Pi homeostasis network. Taken together, these results demonstrate the activation of AtPAP17 and AtPAP26 genes to buffer against the loss of function of each other, and this compensation relationship is vital for Arabidopsis growth and development.